2000
DOI: 10.1046/j.1365-2125.2000.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of ziprasidone in subjects with normal and impaired renal function

Abstract: Aims To assess whether renal impairment in¯uences the pharmacokinetics of ziprasidone, and to determine whether ziprasidone is cleared via haemodialysis. Methods Thirty-nine subjects with varying degrees of renal impairment were enrolled into an open-label, multicentre, multiple-dose study and assigned to four groups according to their renal function: normal (group 1, creatinine clearance >70 ml min x 1 ); mildly impaired (group 2, creatinine clearance 30±60 ml min x 1 ); moderately impaired (group 3, creatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Dosage adjustment is recommended in renal disease [60]. The pharmacokinetics of olanzapine, quetiapine, and oral ziprasidone are not altered in renal disease [76,77]. Though the intramuscular formulation of ziprasidone has not been studied in patients with renal impairment, because the cyclodextrin excipient is renally cleared it is suggested that it be administered with caution to patients with renal impairment [78].…”
Section: Resultsmentioning
confidence: 99%
“…Dosage adjustment is recommended in renal disease [60]. The pharmacokinetics of olanzapine, quetiapine, and oral ziprasidone are not altered in renal disease [76,77]. Though the intramuscular formulation of ziprasidone has not been studied in patients with renal impairment, because the cyclodextrin excipient is renally cleared it is suggested that it be administered with caution to patients with renal impairment [78].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the molecular weight of triamterene is 253 g/mol, meaning that 1 nM is equal to 0.253 ng/mL, if our calculated Ki is 31.3 nM, it is equivalent to 7.9 ng/mL, below the maximal concentration of 125 ng/mL that was achieved in humans after an oral single dose of 100 mg . Regarding ziprasidone, using a similar approach, the plasma concentrations obtained after a therapeutic oral dose of 20 mg was 47 ng/mL, that is higher than 4 ng/mL (9.7 nM) corresponding to our calculated Ki for this drug.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the pharmacokinetics of risperidone were not significantly altered in cirrhosis patients [70]. Unfortunately, there is no liver function test, or combination of tests, that can quantify impairment of liver function in a manner analogous to serum creatinine or creatinine clearance for renal impairment [71]. Because antipsychotics are considerably protein bound, the reduced protein production in chronic liver disease results in an increased free fraction of the medication.…”
Section: Liver Diseasesmentioning
confidence: 98%
“…For the other atypical antipsychotics, dose adjustments in renal failure have not specifically been recommended. For example, the pharmacokinetics of ziprasidone are not significantly affected by mild-moderate renal impairment or by hemodialysis [71].…”
Section: Renal Diseasesmentioning
confidence: 99%